Potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material and preparation method thereof

Preparation of potassium, magnesium, silicon ternary co-doped vanadium phosphate positive electrode material through sol-gel method, solving the problem of insufficient rate performance and cycle stability of vanadium phosphate in sodium ion batteries, and achieving higher electrochemical performance and battery life.

CN119153662APending Publication Date: 2024-12-17CHINA UNIV OF PETROLEUM (EAST CHINA)

Patent Information

Application Number
CN202411420592.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode material sodium vanadium phosphate (NVP), due to its high Na+ diffusion ability and poor electronic conductivity, has poor rate performance and cycle stability, which limits its practical application.

Method used

The lattice structure of the material is adjusted by sol-gel method, and the Na+ migration channel is broadened and the electron conductivity and structural stability are improved by K+, Mg2+ and Si4+ ion doping. .

Benefits of technology

It significantly improves the rate performance and cycle stability of the material, extends the battery life, and improves the electrochemical performance through small particle size and uniform particle size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153662A_ABST
    Figure CN119153662A_ABST
Patent Text Reader

Abstract

The invention provides a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of energy materials. The positive electrode material is formed by doping a Na site with K < + > ions, doping a V site with Mg < 2 + > ions and doping a P site with Si < 4 + > ions, and the chemical formula of the positive electrode material is Na < 3.1 > KxV < 2-x > Mgx (PO4) 2.9 (SiO4) 0.1 / C (x = 0.03, 0.05, 0.07); according to the invention, ammonium metavanadate, sodium acetate and ammonium dihydrogen phosphate are used as raw materials, potassium dihydrogen phosphate, magnesium acetate tetrahydrate and tetraethyl silicate are used as doping sources, citric acid monohydrate is used as a chelating agent, and the potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate electrode material is prepared by a solution gel method, so that the electronic conductivity is improved, the rate capability and the cycle stability are improved, and the preparation method is simple and convenient. The preparation method has a good application prospect in sodium ion battery positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery technology, and specifically relates to a sodium ion battery positive electrode material modified by three-element synergistic doping and a preparation method thereof. Background Art

[0002] At present, the world is in an era of increasing energy demand to meet the development needs of the rapidly developing modern society. Energy comes in various forms, mainly relying on oil, coal, natural gas, etc., but these energy sources are limited and will cause serious pollution to the environment. Therefore, we must develop clean, efficient, and renewable new energy. Lithium-ion batteries have been widely used in many fields, but the low lithium content makes it difficult for lithium-ion batteries to be used on a large scale.

[0003] Sodium and lithium belong to the same main group, have similar physical and chemical properties, and have high content in the earth's crust, wide distribution, and low price. They have broad application prospects in the field of large-scale energy storage. Sodium vanadium phosphate (Na3V2(PO4)3, NVP) is a polyanion compound with a unique three-dimensional NASICON structure, which can promote Na + Rapid migration of NVP. It is considered to be the most promising cathode material for sodium ion batteries due to its stable structure, high operating voltage and high capacity. + The diffusion capacity is accompanied by a large bulk structure and poor electronic conductivity, resulting in poor electrochemical performance in terms of rate capability and cycle stability, thus hindering its practical application. By carbon coating, sodium vanadium phosphate / carbon composite materials are prepared, the electronic conductivity of the material is improved, thereby improving the electrochemical activity of sodium vanadium phosphate; by doping ions, the structural stability of the material is improved, the ion diffusion channel is expanded, the ion conductivity is improved, and thus the electrochemical performance of the material is improved.

[0004] At present, most of the existing inventions use the solid phase method to prepare positive electrode materials, but the material composition prepared by the solid phase method is uneven and the particle size distribution is wide. The present invention adopts a sol-gel preparation method, which is simple and easy to implement. The sample prepared by this method has a small particle size and good uniformity. In addition, the modification of the material by single-element doping is often one-sided. The present invention adopts multi-element doping, which not only improves the conductivity of the material, but also enhances the structural stability of the material and prolongs the battery life. The doping of different elements adjusts the lattice of the material and optimizes the migration channel of sodium ions, thereby improving the rate performance and ion diffusion rate of the battery. Summary of the invention

[0005] The object of the present invention is to provide a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material and a preparation method thereof, the method having a simple process. The prepared positive electrode material for sodium ion batteries has a stable structure, enlarged ion diffusion channels, and has good rate performance and cycle stability.

[0006] The present invention first provides a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material, which is composed of K + Ion doping Na, Mg 2+ Ion doping V and Si 4+ The positive electrode material is formed by ion doping at the P position, and the chemical formula of the positive electrode material is Na 3.1 K x V 2-x Mg x (PO4) 2.9 (SiO4) 0.1 / C(x=0.03, 0.05, 0.07).

[0007] The present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, which is prepared by a sol-gel method and comprises the following steps:

[0008] (1) weighing a sodium source, a potassium source, a vanadium source, a magnesium source, a phosphorus source, a silicon source, and a carbon source according to a molar ratio and pouring them into 60 ml of a deionized water solution, stirring them fully in a 50° C. oil bath for 2-4 hours, and raising the temperature to 90° C. and continuing to heat until the deionized water is completely evaporated to form a gel-like substance after the solution turns blue;

[0009] (2) placing the gel-like substance formed in step (1) in a drying oven for drying to form a precursor;

[0010] (3) The precursor formed in step (2) is ground in an agate mortar, and then placed in a tubular furnace and calcined under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.

[0011] The sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium hydroxide; the potassium source is one or more of potassium hydroxide, potassium carbonate, potassium dihydrogen phosphate, and potassium nitrate; the vanadium source is ammonium metavanadate; the magnesium source is one or more of magnesium nitrate, magnesium acetate, and magnesium sulfate; the phosphorus source is one or two of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; the silicon source is tetraethyl orthosilicate; and the carbon source is one or more of sucrose, glucose, and citric acid monohydrate;

[0012] As a further solution of the present invention: the drying temperature in step (2) is 100°C-180°C.

[0013] As a further solution of the present invention: the high temperature calcination experimental conditions in step (3) are: pre-sintering at 350°C for 3h, and then final sintering at 800°C for 8h, the heating rate is 3-6°C / min, and the inert atmosphere is nitrogen or argon.

[0014] The present invention also provides a method for preparing a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode sheet, the steps of which include:

[0015] (1) Grinding the active positive electrode material, conductive additive and binder in a mass ratio of 8:1:1 and 7:2:1;

[0016] (2) adding an appropriate amount of N-methylpyrrolidone to the powder in step (1), and stirring on a magnetic stirrer for 0.5-8 h to obtain a slurry;

[0017] (3) The slurry is evenly coated on the aluminum foil with a coater, with a thickness of 100-400 μm;

[0018] (4) Drying in a vacuum drying oven at 80-120°C for 8-12 hours;

[0019] (5) Cut the electrode into discs to obtain the positive electrode of the battery.

[0020] Application of the positive electrode material in sodium ion batteries.

[0021] The beneficial effects of the present invention are embodied in:

[0022] (1) Citric acid monohydrate acts as both a chelating agent and a reducing agent, and part of it participates in the reduction reaction, making V 5+ Restore to V 3+ The rest of the carbon source forms a conductive carbon layer on the surface of the material, which improves the conductivity of the material and thus improves the electrochemical performance of the material. The modified material has good rate performance and cycle stability.

[0023] (2) Through K + Ion doping Na, Mg 2+ Ion doping V and Si 4+ Ion doping P site, potassium ions extend the unit cell volume along the c-axis, and the other two ions cause the crystal volume to expand along other directions. + The migration channel of Mg increases the stability of the crystal framework. + Ion-doped V in NVP 3+ ions, and accommodate the additional Na + ions to maintain charge balance. During the charge and discharge process, additional Na + , higher capacity can be obtained.

[0024] (3) The particle size of the material prepared by the present invention is reduced, the agglomeration phenomenon is reduced, and the specific surface area of ​​the material is increased, which is conducive to better wetting of the electrolyte and improves the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray diffraction (XRD) pattern of the sodium ion battery positive electrode material obtained in Example 2 of the present invention;

[0026] Figure 2 This is a scanning electron microscope (SEM) morphology image of the sodium ion battery positive electrode material obtained in Example 2 of the present invention;

[0027] Figure 3 This is a comparison chart of the cycle performance of the target product obtained in Example 2 of the present invention and in Comparative Example 1 after 200 cycles at a 1C rate;

[0028] Figure 4 This is a comparison chart of the rate performance of the sodium ion battery positive electrode materials obtained in Example 2 of the present invention and Comparative Example 1;

[0029] Figure 5 The figure is a comparison chart of the cycle performance of the target product obtained in Example 2 of the present invention and in Comparative Example 1 after 500 cycles at a 5C rate. Specific implementation methods

[0031] In order to make the technical method of the embodiment of the present invention clearer, the technical method of the embodiment will be clearly described below. The described embodiment is only a part of the embodiment of the present invention, not all of the embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0032] Embodiment 1:

[0033] Step 1: Preparation of Na by sol-gel method 3.1 K 0.03 V 1.97 Mg 0.03 (PO4) 2.9 (SiO4) 0.1 / C positive electrode material

[0034] (1) According to the molar ratio, 1.05 g of citric acid monohydrate, 1.055 g of sodium acetate, 0.576 g of ammonium metavanadate, 0.01 g of potassium dihydrogen phosphate, 0.016 g of magnesium acetate tetrahydrate, 0.825 g of ammonium dihydrogen phosphate, and 0.021 g of tetraethyl orthosilicate were weighed and added to 60 ml of deionized water in sequence. The mixture was stirred in an oil bath at 50° C. for 2-3 hours. After the solution turned blue, the temperature was adjusted to 90° C. and stirring was continued until the solution turned into a blue gel.

[0035] (2) placing the gel-like substance formed in step (1) in a drying oven at 120° C. to dry to form a precursor;

[0036] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;

[0037] Step 2: Preparation of Na 3.1 K 0.03 V 1.97 Mg 0.03 (PO4) 2.9 (SiO4) 0.1 / C positive electrode

[0038] (1) The positive electrode material prepared above was mixed with Super P and polyvinylidene fluoride in a mass ratio of 7:2:1, hand-grinded until the mixture was uniformly mixed, and an appropriate amount of N-methylpyrrolidone was added. The mixture was placed on a magnetic stirrer and stirred for 30 minutes to form a slurry. The slurry was coated on an aluminum foil with a thickness of 100 μm, and then placed in a vacuum drying oven at 120° C. and dried for 12 hours to obtain a pole piece;

[0039] (2) 2032 button cells were assembled using metallic sodium as the negative electrode. The entire assembly process was carried out in a glove box filled with argon. The assembly order was: negative electrode shell, metallic sodium, glass fiber separator (GF / D), electrolyte (1M NaClO4 in EC:DC=1:1 vol%), positive electrode sheet (14 mm), gasket, elastic ring, positive electrode shell; the charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System at 5C (1C=117.6 mA g -1 ) current density and in the voltage range of 2.3-4.2 V, the capacity retention rate was 82% after 500 cycles.

[0040] Comparative Example 1:

[0041] The preparation process of the sodium ion battery positive electrode material with the molecular formula Na3V2(PO4)3 / C is exactly the same as that in Example 1, and the preparation process of the pole piece and the battery assembly and testing process are the same as those in Example 1.

[0042] Embodiment 2:

[0043] Step 1: Preparation of Na by sol-gel method 3.1 K 0.05 V 1.95 Mg 0.05 (PO4) 2.9 (SiO4) 0.1 / C positive electrode material

[0044] (1) According to the molar ratio, 1.05 g of citric acid monohydrate, 1.055 g of sodium acetate, 0.570 g of ammonium metavanadate, 0.017 g of potassium dihydrogen phosphate, 0.027 g of magnesium acetate tetrahydrate, 0.819 g of ammonium dihydrogen phosphate, and 0.021 g of tetraethyl orthosilicate were weighed and added to 60 ml of deionized water in sequence. The mixture was stirred in an oil bath at 50° C. for 2-3 hours. After the solution turned blue, the temperature was adjusted to 90° C. and stirring was continued until the solution turned into a blue gel.

[0045] (2) placing the gel-like substance formed in step (1) in a drying oven at 120° C. to dry to form a precursor;

[0046] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;

[0047] Step 2: Preparation of Na 3.1 K 0.05 V 1.95 Mg 0.05 (PO4) 2.9 (SiO4) 0.1 / C positive electrode sheet, the preparation process is the same as that of Example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System.

[0048] Figure 1 This is the XRD image of the target product obtained in Example 2. As can be seen from the figure, the XRD results show that all characteristic peaks indicate the R-3C space group, which is consistent with the NVP characteristic structure. It can be considered that the introduction of the three elements will not destroy its crystal composition.

[0049] Figure 2 This is the SEM image of the target product obtained in Example 2. The sample particle size is small, which is conducive to the penetration of the electrolyte.

[0050] Figure 3 The positive electrode material described in Example 2 is 1C (1C = 117.6 mA g -1 ) The cycle stability curve of 200 cycles under the current density of 1.5 200 cycles. It can be seen from the figure that this material has a high discharge specific capacity of 98.62 mAg when applied to sodium ion batteries. -1 , after 200 cycles, it can still reach 94.2mAg -1 , the capacity retention rate is as high as 94.5%.

[0051] Figure 4The rate performance curves of Example 2 and Comparative Example 1 at current densities of 0.2C, 0.5C, 1C, 5C, 10C, 20C, 30C, and 0.2C in the voltage range of 2.3-4.2V.

[0052] Figure 5 The positive electrode material described in Example 2 is 5C (1C = 117.6mAg -1 ) current density and in the voltage range of 2.3-4.2V, the cycle stability curve after 500 cycles, the capacity retention rate after 500 cycles is 89.3%. This is because the incorporation of the three elements expands the ion diffusion path and reduces the particle size, increases the specific surface area, improves the electronic conductivity, improves the electrochemical performance of the material, and improves the cycle stability.

[0053] Embodiment 3:

[0054] Step 1: Preparation of Na by sol-gel method 3.1 K 0.07 V 1.93 Mg 0.07 (PO4) 2.9 (SiO4) 0.1 / C positive electrode material

[0055] (1) According to the molar ratio, 1.05 g of citric acid monohydrate, 1.055 g of sodium acetate, 0.564 g of ammonium metavanadate, 0.024 g of potassium dihydrogen phosphate, 0.038 g of magnesium acetate tetrahydrate, 0.813 g of ammonium dihydrogen phosphate, and 0.021 g of tetraethyl orthosilicate were weighed and added to 60 ml of deionized water in sequence. The mixture was stirred in an oil bath at 50° C. for 2-3 hours. After the solution turned blue, the temperature was adjusted to 90° C. and stirring was continued until the solution turned into a blue gel.

[0056] (2) placing the gel-like substance formed in step (1) in a drying oven at 120° C. to dry to form a precursor;

[0057] (3) The precursor formed in step (2) was ground in an agate mortar and transferred to a crucible, which was then placed in a tube furnace and sintered in an argon atmosphere, first at 350°C for 3 h, then at 800°C for 8 h, with a heating rate of 5°C min -1 After cooling naturally to room temperature, take out the battery positive electrode material;

[0058] Step 2: Preparation of Na 3.1 K 0.07 V 1.93 Mg 0.07 (PO4) 2.9 (SiO4) 0.1 / C positive electrode sheet, the preparation process is the same as Example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System at 1C (1C = 117.6mAg -1 ) current density and in the voltage range of 2.3-4.2 V, the capacity retention rate was 85.3% after 200 cycles.

Claims

1. A potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material, characterized in that: The potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate electrode material is composed of K + Ion doping Na, Mg 2+ Ion doping V and Si 4+ Ion doping P position is formed, the chemical formula of the positive electrode material is Na 3.1 K x V 2-x Mg x (PO4) 2.9 (SiO4) 0.1 / C(x=0.03, 0.05, 0.07).

2. The method for preparing a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode material according to claim 1, characterized in that: The preparation is carried out by a sol-gel method, comprising the following steps: (1) weighing a sodium source, a potassium source, a vanadium source, a magnesium source, a phosphorus source, a silicon source, and a carbon source according to a molar ratio and pouring them into 60 ml of a deionized water solution, stirring them fully in a 50° C. oil bath for 2-4 hours, and raising the temperature to 90° C. and continuing to heat until the deionized water is completely evaporated to form a gel-like substance after the solution turns blue; (2) placing the gel-like substance formed in step (1) in a drying oven for drying to form a precursor; (3) The precursor formed in step (2) is ground in an agate mortar, and then placed in a tubular furnace and calcined under an inert atmosphere to obtain a positive electrode material for a sodium ion battery.

3. The preparation method according to claim 2, characterized in that: The sodium source in step (1) is one or more of sodium carbonate, sodium nitrate, sodium acetate and sodium hydroxide; The potassium source is one or more of potassium hydroxide, potassium carbonate, potassium dihydrogen phosphate, and potassium nitrate; The vanadium source is ammonium metavanadate; The magnesium source is one or more of magnesium nitrate, magnesium acetate and magnesium sulfate; The phosphorus source is one or two of diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; The silicon source was tetraethyl orthosilicate; The carbon source is one or more of sucrose, glucose and citric acid monohydrate.

4. The preparation method according to claim 2, characterized in that: The drying temperature in step (2) is 100°C-180°C.

5. The preparation method according to claim 2, characterized in that: The high temperature calcination experimental conditions in step (3) are: pre-sintering at 350°C for 3h, and then final sintering at 800°C for 8h, with a heating rate of 3-6°C / min, and the inert atmosphere is nitrogen or argon.

6. A preparation method for a potassium-magnesium-silicon ternary co-doped sodium vanadium phosphate positive electrode sheet, which is characterized by comprising the following steps: (1) Grinding the active positive electrode material, conductive additive and binder in a mass ratio of 8:1:1 and 7:2:1; (2) adding an appropriate amount of N-methylpyrrolidone to the powder in step (1), and stirring on a magnetic stirrer for 0.5-8 h to obtain a slurry; (3) The slurry is evenly coated on the aluminum foil with a coater, with a thickness of 100-400 μm; (4) Drying in a vacuum drying oven at 80-120°C for 8-12 hours; (5) Cut the electrode into discs to obtain the positive electrode of the battery.

7. The preparation method according to claim 6, characterized in that: The binder in step (1) is one or more of polyvinylidene fluoride or polyacrylic acid, sodium carboxymethyl cellulose, and sodium alginate, and the conductive agent is one or more of Super P, carbon black, and Ketjen black.

8. Use of the positive electrode material according to claim 1 in a sodium ion battery.

Citation Information

Patent Citations

  • Material with mixture of ions with sodium vanadium phosphate cathode material coated by carbon and preparing method thereof

    CN106328911A

  • Potassium-lanthanum-silicon ternary co-doped sodium vanadium phosphate electrode material as well as preparation method and application thereof

    CN113659146A

  • Graphene composite potassium-silicon co-doped sodium vanadium phosphate composite material and preparation and application thereof

    CN114944479A

  • Preparation method of transition metal ion doped sodium vanadium phosphate positive electrode material

    CN114975992A

  • Battery material and preparation method and application thereof

    CN117623260A

Cited By

  • Chlorine tungsten anion and cation co-doped sodium vanadium phosphate positive electrode material and preparation method thereof

    CN119725447A